HEART FAILURE: UNDERSTANDING AND MODERN TREATMENT METHODS (Modern education and development, 2025)
Heart failure (HF) is a complex clinical syndrome characterized by the heart's inability to pump sufficient blood to meet the body's metabolic demands. This article explores the pathophysiology, diagnostic criteria, and contemporary treatment strategies for HF, emphasizing evidence-based approaches. Key advancements in pharmacological therapies (e.g., SGLT2 inhibitors, ARNIs) and device-based interventions (e.g., CRT, LVADs) are discussed. Early diagnosis and multidisciplinary management remain crucial for improving patient outcomes.